Synthesis and electrical characterization of tungsten doped Pb(Zr0.53Ti0.47)O-3 ceramics obtained from a hybrid process - Santos, D. M.; Simoes, A. Z.; Zaghete, M. A.; Paiva-Santos, C. O.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Pure and W-doped PZT ceramics (PZT and PZTW) were prepared by a hybrid process consisting in the association of polymeric precursor and partial oxalate methods. The phase formation was investigated by simultaneous thermal analysis (TG/DSC) and X-ray diffraction (XRD). The effect of W doping PZT and their electrical properties was evaluated. Substitution of W by Ti leads to an increase of Curie temperature and broadening of dielectric constant. A typical hysteresis loop was observed at room temperature and the remnant polarization was increased with the content of W. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ceramics; sintering; dielectric properties; ferroelectricity